Use of Cannabis-Based Medical Products for Pediatric Health Conditions: A Systematic Review of the Recent Literature - Mitchell L. Doucette; Dipak Hemraj; David J. Casarett; D. Luke Macfarlan; Emily Fisher (Medical Cannabis and Cannabinoids)
Introduction: Cannabis policy is rapidly changing in the USA and across the globe, with 24 states legalizing cannabis for adult use and 38 states making medical cannabis available for those with qualified conditions. Building on prior evidence, we reviewed the recently published literature (from the past 5 years) focused on the treatment effects of naturally derived medical cannabis products within the pediatric population. Methods: We conducted a systematic literature review of three electronic databases using MeSH terms and free-text. A study was eligible for inclusion if it investigated the efficacy of medical cannabis for any condition, it was published in 2019 or later, and the mean age of participants was under 21. We excluded studies that tested the effect of pharmaceutical cannabis-derived drug products. Results: We identified a total of 10 studies that met our inclusion/exclusion criteria. Of the 10, 2 utilized a double-arm randomized control trial (RCT) design, 3 used a single-arm trial design, and the remaining were observational studies, a case series, or a qualitative design. Aside from autism spectrum disorder (ASD) (n = 4), studies focused on cancer, treatment-resistant epilepsy, and Sturge-Weber syndrome (SWS). Four of the five single- or double-arm trials used a CBD:THC compound in a specific ratio as treatment. Both RCTs found significant improvement in ASD-related validated measures. Other studies found general improvements in validated measures of efficacy for SWS and epilepsy. Minimal adverse events were reported. Conclusion: In the pediatric population, emerging evidence, combined with existing literature, suggests medical cannabis may be beneficial for quality-of-life symptoms related to specific conditions, like cancer, ASD, treatment-resistant epilepsy, and SWS. More clinical trial data are necessary to establish medical cannabis as an addition to established medical guidelines.